Potential financial loss and risk factors for hamstring muscle injuries in elite male Brazilian soccer players: a season-long prospective cohort pilot study - Oliveira-Júnior, Otaviano; Gabbett, Tim J.; Bittencourt, Natalia F. N.; Quintão, Roberto C.; Reis, Guilherme F.; Claudino, João G.; Lasmar, Rodrigo C. P.; Leopoldino, Amanda A. O. (Frontiers in Sports and Active Living, 2024)
Purpose: The aim of this pilot study was to analyze the potential financial loss and a range of potential risk factors for hamstring muscle injuries in elite Brazilian soccer. Methods: Thirty-four male players (age: 25 ± 6 years; stature: 180 ± 8 cm; body mass: 78 ± 9 kg; minutes played in matches: 1975 ± minutes) from an elite professional soccer club were monitored during a 12-month season. Muscle injury was identified by magnetic resonance imaging and the severity was defined according to the number of days away: minimal (1-3 days), mild (4-7 days), moderate (8-28 days), severe (>28 days).Potential financial loss due to the team's under achievements was determined. Dorsiflexion range of motion, eccentric knee flexor strength and isokinetic tests were performed during the pre-season.Association between dependent variables and the occurrence of injury was evaluated. Results: Nine hamstring muscle injuries with moderate severity were found in 8 athletes. Recovery time was 22 days off the field on average. Potential financial loss was $-43.2 million USD and earnings on merit money was 21%. Previous injury, increased flexor deficit 60º/sec and increased flexor fatigue index 300º/sec were all associated with a greater chance of hamstring muscle injury. Ankle dorsiflexion range of motion was significantly lower in the injured group (35.6 ± 3° vs 39.1 ± 4.9°; p = 0.017, effect size = -0.74). Conclusion: High financial burden was found in elite Brazilian soccer during one full season.Injured athletes had high hamstring fatigue index, knee flexor strength deficit, ankle range of motion restriction and previous hamstring muscle injury when compared to non-injured athletes. Therefore, preventive approaches in professional soccer players with previous hamstring injuries should be a priority.